The burden of invasive pneumococcal disease in children with underlying risk factors in North America and Europe. Issue 1 (19th July 2013) - Rose, M. A.; Christopoulou, D.; Myint, T. T. H.; de, I.
Summary Background Characterisation of risk groups who may benefit from pneumococcal vaccination is essential for the generation of recommendations and policy. Methods We reviewed the literature to provide information on the incidence and risk of invasive pneumococcal disease (IPD) in at‐risk children in Europe and North America. The PubMed database was searched using predefined search terms and inclusion/exclusion criteria for papers reporting European or North American data on the incidence or risk of IPD in children with underlying medical conditions. Results Eighteen references were identified, 11 from North America and 7 from Europe, with heterogeneous study methods, periods and populations. The highest incidence was seen in US children positive for human immunodeficiency virus infection, peaking at 4167 per 100, 000 patient‐years in 2000. Studies investigating changes in incidence over time reported decreases in the incidence of IPD between the late 1990s and early 2000s. The highest risk of IPD was observed in children with haematological cancers or immunosuppression. Overall, data on IPD in at‐risk children were limited, lacking incidence data for a wide range of predisposing conditions. There was, however, a clear decrease in the incidence of IPD in at‐risk children after the introduction of 7‐valent pneumococcal conjugate vaccine into immunisation programmes, as previously demonstrated in the general population. Conclusion Despite the heterogeneity of the studies identified, the available data show a substantial incidence of IPD in at‐risk children, particularly those who are immunocompromised. Further research is needed to determine the true risk of IPD in at‐risk children, particularly in the post‐PCV period, and to understand the benefits of vaccination and optimal vaccination schedules.